TINJAUAN PERATURAN BUPATI NOMOR: 45 TAHUN 2015 TENTANG TATA CARA PENCEGAHAN DAN PENANGGULANGAN HIV/AIDS TERHADAP PERKEMBANGAN PROSTITUSI KABUPATEN BANYUWANGI - Hary Priyanto (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2018)
AbstractProstitution is a negative thing. For those who undergo these activities are considered scum of society. But in a certain sense, the existence of prostitution is considered a positive thing. Because the presence of prostitution is able to impact on the prevention of rape. In addition, prostitution activities are also tolerated for reasons of economic factors, whether it is the fulfillment of the economic needs of the family, or other people whose work by utilizing the existence of the prostitution practice. In Banyuwangi Regency, there are 14 locations of prostitution localization. Yet, undetected places as the impact of pathological behavior. By the proliferation of activities just precisely open the door of the most vital and deadly diseases, namely HIV / AIDS. Therefore, in order to handle the HAV / AIDS, the Government of Banyuwangi Regency makes a policy in the form of Regent Regulation of Banyuwangi Number: 45 / 2015, About: The Prevention and Control procedure of HIV / AIDS. The existence of the Government policy of Banyuwangi Regency just precisely impact on the progress of HIV / AIDS case that more increased.Keywords: Prostitution, HIV / AIDS, Banyuwangi Regency